Conserving Canada's musk-oxen - Canada. Dept. of the interior. Northwest territories and Yukon branch.; Anderson, Rudolph Martin, 1876-1961; Hoare, William H. B. (Ottawa, F. A. Acland, printer to the King, 1930)
At head of title: Department of the Interior. Hon. Thomas G. Murphy, minister. W.W. Cory, C.M.G., deputy minister. North West Territories and Yukon Branch. O.S. Finnie, director. "Notes on the musk-ox and the caribou, by R.M. Anderson, PH. D.": p.49-53. Mode of access: Internet.